A dimensão formativa do cinema e a catarse como categoria psicológica : um diálogo com a psicologia histórico-cultural de Vigotski - Ramos, Santiago Daniel Hernandez-Piloto (2015)
The academic research deals with the relationship between the aesthetics of film and the sensitive dimension of the viewer and takes as its central axis of this dialogue the concept of catharsis at the Psychology of Art Vygotsky (1999b). The objective of the research is to understand how the concept of catharsis can contribute with the reflection in the field of education of the senses (aesthetic training) and if he can create the conditions and possibilities to transform qualitatively the viewer in contact with the film / cinema. The methodology is eminently of theoretical-reflective nature. Used the study of the literature, analysis of the scholarly works focusing on catharsis key concept. The research takes as its premise that, in contemporary society, the cinema is one of the main routes of aesthetic, with a significant presence in the process of formation of individuality in different social contexts. The reflective dimension of the survey also operates from the analysis of the film Fresa y Chocolate (1993), by Cuban filmmaker Tomas Gutierrez Alea. A first hypothesis considers that formative dimension of cinema only reaches its maximum concreteness when the viewer, the experience with the film, is elevated to a higher level of qualitative transformation from opposing emotions aroused by the aesthetic narrative - conflict between content and form. A second hypothesis that considers the aesthetics perspective of Gutierrez Alea, in particular Fresa y Chocolate (1993) approaches the concept developed by Vygotsky of catharsis. Thus, this concept can contribute to, in the field of education, broaden reflection on the understanding of the aesthetic response that the viewer experiences in contact with the film, whose function goes beyond the representation of reality, it can be considered the viewer's own vision of social reality. Catharsis, as the foundation of aesthetic response experienced by the viewer with the work, is in a complex transformation sensitive and also of one's consciousness and perception of objective reality.